Kontribusi Permainan Tradisional Dalam Meningkatkan Kondisi Fisik Siswa Sekolah Dasar Usia 10-12 Tahun - Hadid, Yahya Al; Syaukani, Agam Akhmad (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
This study aims to determine the contribution of traditional games to improving the physical condition of students aged 10-12 years and to determine how much traditional games contribute to improving the physical condition of students aged 10-12 years. The research design is pre-test-post-test control group design. The research location is at SD Muhammadiyah 23 Surakarta, the research time was carried out in March 2024 to April 2024. The research subjects were 25 students in class V C as the experimental class and 26 students in class V A as the control class. The data collection technique used the Indonesian Student Fitness Test (TKSI). The collection method uses the test method. The analysis used is the independent sample t-test. The results of the statistical analysis of the independent sample t-test results obtained a calculated t value> t table (2.414 > 2.021) a significance value of 0.020 <0.05, it can be concluded that there is a contribution of traditional games to improving the physical condition of students aged 10-12 years. The average value in the experimental group TKSI through traditional games 17.84 > from the average of 16.65 in the control group without going through traditional games. The average value of the pre-test of the experimental class was 16.08 after receiving treatment through traditional games the average value of the post-test increased to 17.84. In the control group the average physical condition of the pre-test was 16.19 and the average value of the post-test was 16.65. Therefore, it can be concluded that traditional games (experimental class) are quite effective in improving the physical condition of students aged 10-12 years at SD Muhammadiyah 23 Surakarta.